RANCANGAN DAN UJI COBA PELATIHAN RESILIENSI UNTUK MENURUNKAN PSYCHOLOGICAL DISTRESS PADA IBU YANG MEMILIKI ANAK PENDERITA ACUTE LYMPHOBLASTIC LEUKEMIA (ALL) - R. Fauziah Febrianni Fathurochman (QUANTA, 2017)
The most common types of leukemia (blood cancer) that Indonesia children have are Acute Lymphoblastic Leukemia (ALL) considered to have a high mortality rate. One contributing factor is the inability of parents to adapt to changes in the child's condition on the induction phase of treatment such as nausea, vomiting, fatigue, pain, infection, mucositis (wound on the mouth), alopecia (hair loss), mood disorders and anemia. Changes in the condition of the child make the mothers, as the main caregiver, deal with the distressful situation so that the mother often abandon the treatment and not obedient to the doctor's advice that basically can affect the healing process of children. Therefore, the mother needs an inner ability to adapt to the condition of the child's illness through training. This ability is called by Grotberg (1995) as Resilience. By providing knowledge on the resilience-forming factors of I Have, I Am, and I Can it is highly expected that the mothers having ALL children in the induction phase will be able to adapt to changing child's condition. The research design used is one group pretest-posttest. The measurement of Psychological Distress uses K10 questionnaires; while to know the picture of resilience mother the interview was also used. Data processing is done by using descriptive statistical analysis and content analysis. The conclusions show that (1) the design of Resilient Training Modules tested can reduce the psychological distress score on the mother; (2) In general, the activities, methods, tools, and facilitators in the resilience training module is already in accordance with the participants' need to increase resilience capacity and reduce psychological distress; (3) Decreased physical condition of children such as diarrhea, oral bleeding, etc. becomes a risk factor that can increase the score of mother distress.